2015
DOI: 10.1021/es5055918
|View full text |Cite
|
Sign up to set email alerts
|

High Exposure of California Firefighters to Polybrominated Diphenyl Ethers

Abstract: Concern about persistent organic pollutants (POPs) in Californians prompted the state's biomonitoring program to conduct a study in firefighters, who are occupationally exposed to high levels of POPs. In this work we present serum concentrations of several classes of POPs (polybrominated diphenyl ethers [PBDEs], polychlorinated biphenyls [PCBs], and organochlorine pesticides [OCPs]) in 101 Southern California firefighters. Despite recently reported declining trends of PBDEs in Californians, high levels were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 45 publications
(82 reference statements)
3
54
1
Order By: Relevance
“…For example, in the biomonitoring study of the California firefighters, lower serum levels of PBDEs were found in firefighters who practiced more hygienic turnout gear storage. 16 In the current analysis, we were unable to assess the impact of turnout gear storage practices on vacuum-dust PBDE levels, as the small number of firefighters surveyed in the participating fire stations was not sufficient to represent station-wide practices. Our ability to identify statistical relationships between explanatory factors and chemical levels in fire station dust was also limited by our small sample size (N = 20 stations, 27 samples).…”
Section: ■ Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, in the biomonitoring study of the California firefighters, lower serum levels of PBDEs were found in firefighters who practiced more hygienic turnout gear storage. 16 In the current analysis, we were unable to assess the impact of turnout gear storage practices on vacuum-dust PBDE levels, as the small number of firefighters surveyed in the participating fire stations was not sufficient to represent station-wide practices. Our ability to identify statistical relationships between explanatory factors and chemical levels in fire station dust was also limited by our small sample size (N = 20 stations, 27 samples).…”
Section: ■ Discussionmentioning
confidence: 96%
“…16 In this companion study, dust samples from 20 of these fire stations (3 in 2010 and 17 in 2011) were collected during on-site surveys. Participating fire stations were selected to represent a variety of emergency response volume and building age.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…One being the fact that PBDEs are in fact present in firefighter equipment [76]. Second, California firefighters themselves that have been studied and results from two different populations show that due to their activities their sera contain levels of PBDEs far above those found in the general California population [77, 78]. Third, the dust from a total of 20 fire stations in Southern California contained higher levels of PBDEs compared to dust in residential homes [79].…”
Section: Resultsmentioning
confidence: 99%
“…Samples were thawed and aliquoted for PBDE and lipids measurements. Automated solid phase extraction (SPE; Biotage, Uppsala, Sweden) and gas chromatography/high resolution mass spectrometry (GC-HRMS, DFS, ThermoFisher, Bremen, Germany) were used for the analysis of PBDEs 27 . Briefly, thawed serum samples (2 mL) were fortified with a panel of 13 C 12 labeled surrogate mix standards (Wellington Laboratories, Inc., Guelph, Ontario, Canada) and mixed well.…”
Section: Methodsmentioning
confidence: 99%